Change from аbove, language contact, and individual change in Ælfric’s linguistic terminology - Yakovenko, Yekaterina (Adam Mickiewicz University, 2019)
The paper focuses on linguistic terminology used by Ælfric (10th c.) in his translation of an anonymous Latin grammar (Excerptiones de arte grammatica anglicе) going back to Priscian and Donatus’ works. Ælfric’s grammatical metalanguage, comprising loan words, semantic loans, loan translations, and periphrastic expressions created for explanatory purposes, is characterized by great diversity. A question arises whether these terms, remaining occasional, made any impact on the language system and can be thus evaluated as change from above. The paper combines a traditional semantic, morphological, and functional description of Ælfric’s terminology and its consideration within the frame of sociolinguistics; the analysis is supplemented by a cross-linguistic study of Ælfric’s terms with remarks on other Germanic languages. The results achieved enable us to argue that Ælfric’s linguistic terminology, being innovative, displays some features of change from above, arising from language contact and individual change.
Keywords: change from above; language contact; metalanguage; loanwords; semantic loans; loan translations; code-switching; terminology